Treatment of canine leishmaniosis: An update. - SARIDOMICHELAKIS (Μ. Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ), M. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The drugs, currently recommended in the treatment of canine leishmaniosis, include meglumine antimonate, allopurinol, paromomycin (aminosidine) and amphotericin B. With the exception of meglumine antimonate, where an optimal dosage has been established (75 mg/Kg BW, every 12 hours, SC), that of allopurinol (10-20 mg/Kg, BW BID, per os), paromomycin (5-10 mg/Kg BW BID, SC or IM) and amphotericin Β (0,5-0.8 mg/Kg BW, 2-3 times weekly, IV, up to a total dose of 8-15 mg/Kg BW), still remains empirical. Although the side effects are relatively few and harmless with the use of meglumine antimonate and allopurinol, they are often life-threatening with paromomycin (ototoxic, nephrotoxic) or amphotericin Β(nephrotoxic). Although the current antileishmanial medications result in the clinical cure of the affected animals and may decrease the contamination potential of sandflies, a parasitological cure is not but occasionally achieved. Therefore, prolonged administration of allopurinol, with or without the intermittent use of meglumine antimonate, is recommended in an attempt to avoid clinical flare-ups. However, repeated cycles of treatment with meglumine antimonate may lead to the emergence of resistant Leishmania spp clones. Withdrawal of medication is justified only when two PCR tests, done on bone marrow samples, 6-months apart, are negative. In the future, the use of cytokines produced by activated Th-1 cells (INF-γ, IL-2, IL-12), may resolve the controversial issue of permanent cure in the dog.